2011
DOI: 10.1177/0956797611413935
|View full text |Cite|
|
Sign up to set email alerts
|

Culturally Divergent Responses to Mortality Salience

Abstract: Two experiments compared the effects of death thoughts, or mortality salience, on European and Asian Americans. Research on terror management theory has demonstrated that in Western cultural groups, individuals typically employ self-protective strategies in the face of death-related thoughts. Given fundamental East-West differences in self-construal (i.e., the independent vs. interdependent self), we predicted that members of Eastern cultural groups would affirm other people, rather than defend and affirm the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 22 publications
3
29
1
Order By: Relevance
“…Second, the present research contributes to TMT's longstanding tenet that while the existence of mechanisms to cope with death are universal, the precise strategies taken to resolve the problem of mortality vary across individuals (e.g., Mikulincer & Florian, 2000;Niemiec et al, 2010), context (e.g.. Cox et al, 2008;Jonas & Fischer, 2006;Harmon-Jones et al, 1997;Routledge et al, 2008;Rutjens et al, 2009;Schmeichel & Martens, 2005;Zhou et al, 2009), and culture (e.g., Ma-Kellams & Blascovich, 2011;Wakimoto, 2006;Yen & Cheng, 2010). Across studies, we demonstrated that striving to enjoy life is a culture-specific response to MS adopted by Easterners but not Westerners.…”
Section: Support For and Expansion Of Tmtmentioning
confidence: 97%
“…Second, the present research contributes to TMT's longstanding tenet that while the existence of mechanisms to cope with death are universal, the precise strategies taken to resolve the problem of mortality vary across individuals (e.g., Mikulincer & Florian, 2000;Niemiec et al, 2010), context (e.g.. Cox et al, 2008;Jonas & Fischer, 2006;Harmon-Jones et al, 1997;Routledge et al, 2008;Rutjens et al, 2009;Schmeichel & Martens, 2005;Zhou et al, 2009), and culture (e.g., Ma-Kellams & Blascovich, 2011;Wakimoto, 2006;Yen & Cheng, 2010). Across studies, we demonstrated that striving to enjoy life is a culture-specific response to MS adopted by Easterners but not Westerners.…”
Section: Support For and Expansion Of Tmtmentioning
confidence: 97%
“…We predicted a large effect size for interaction effect based on previous study (Ma-Kellams and Blascovich, 2011; study 1, f  = 52, study 2, f  = 40). The optimal total sample size to detect an expected large effect size of f 2  =   0.35 (a large effect size) with a power = 0.8 and α  = 0.05 was calculated a priori with the statistical software G-Power (Faul et al , 2009).…”
Section: Methodsmentioning
confidence: 85%
“…Consistent with this notion, Jonas et al (2008) have demonstrated that MS can generate some contrasted behavioral reactions, depending on the situational norm: for example, either pro-social (pro-peace or benevolent) behaviors or pro-self (pro-violence, conservative) behaviors could follow a MS induction. Similarly, Ma-Kellams and Blascovich (2011) have shown that in contrast to European-Americans who evaluate the worldview-threatening others (prostitutes in Study 1 and victim of a car accident in Study 2) more negatively in the MS condition, Asian-Americans evaluate the same targets more positively. These divergent reactions of the Asian- and European-Americans to MS have been attributed to their contrasted self-construals (SC)―interdependent SC that promotes social harmony, and independent SC that promotes self-affirmation, respectively (Markus and Kitayama, 1991).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations